Numerical bio-convective assessment for rate type nanofluid influenced by Nield thermal constraints and distinct slip features - Zhimeng Liu; Shuguang Li; Tooba Sadaf; Sami Ullah Khan; Faris Alzahrani; M. Ijaz Khan; Sayed M. Eldin (Case Studies in Thermal Engineering, 2023)
The performance of energy transportation via implementation of nanoparticles is a hot research area in the modern technological and industrial development era. The boundary-driven Maxwell nanofluid flow over magnetized stretched sheet. The process of bio-convection is accounted under mass and energy transportation. The thermal conductance and activated energy aspects are taken into account. The model is organized by implementing the boundary-layer assumptions. Then, the non-dimensional constraints are utilized to re-construct the mathematical problem. The well-known shooting scheme is incorporated to express the results of problems. The graphical illustrations are reported for the behavior analysis of distinct parameters on quantities of physical and practical importance. The microorganism is augmented due to enlargement in Deborah and magnetic numbers values. An augmentation in temperature is achieved against the incremented thermophoresis and bio-convection constraints.